Religion and spiritual well-being: a qualitative exploration of perspectives of higher education faculty in Qatar and its challenge to western well-being paradigms - Hessa Al-Thani (Frontiers in Psychology)
IntroductionSpiritual well-being (SWB) is a multidimensional and multifaceted concept that encompasses various spheres of human experience, including a person’s spirituality, faith, identity, values, and sense of purpose in life. This study aims to gain a contextualized understanding of how participants affiliated with different higher education institutions in Qatar perceive and experience SWB. It addresses a gap in the literature regarding the influence of cultural and religious factors on the concept of SWB in higher education, particularly in the Qatari context, where cultural factors, especially Islamic values, shape faculty well-being.MethodsAn interpretive qualitative research approach was utilized, focusing on round table (focus group) discussion data obtained from a diverse group of college and university faculty members in Qatar. A purposive sampling technique was employed to recruit participants representing different institutional affiliations. Thematic analysis was used to identify recurring themes and patterns that emerged from the focus groups, viewed through the lens of socio-cultural theory.ResultsFindings reveal that SWB is a very personal and subjective experience, largely influenced by religious beliefs, values, and personal life experiences. Key themes extracted from the data include the intimate relationship between religion (Islam), spirituality, and SWB; the interconnectedness between SWB and adherence to Islamic values and ethics; and the role of SWB in defining identity and in finding meaning and purpose in life.DiscussionThis study contributes to socio-cultural theories of well-being by highlighting how SWB in Qatar challenges and expands the existing Western paradigms of well-being. The practical implications suggest that higher education institutions in Qatar should consider integrating the concept of SWB into faculty support practices, fostering environments that acknowledge and support the role of spirituality in well-being.